SHOULD THE U.S. FEDERAL RESERVE INCREASE THE FEDERAL FUNDS RATE IN 2016? AN ASSESSMENT BASED ON THE NEUTRAL INTEREST RATE - Sánchez Vargas, Armando (Investigación Económica, 2016)
This paper proposes an empirical method to estimate the value of the neutral interest rate in the U.S. and investigates whether the non-conventional monetary policy that has been in effect since the 2008 recession should continue. Specifically, a procedure is established based on a Cointegrated Vector Autoregression (CVAR) model that enables us to conclude that the expansionary monetary policy could continue for at least three more years. Our estimates suggest that the neutral real rate, consistent with full employment and the inflation target in the U.S., will remain negative until 2018. This trend will continue until 2019, when the nominal neutral rate will reach a level of 2%, which remains below the pre-crisis level of 4%. In fact, it seems that the neutral rate has permanently shifted toward a lower level associated with the new fundamentals of the U.S. economy.